Multi Intepretasi Ketertiban Umum Dalam Eksekusi Putusan Arbitrase Asing Di Indonesia - Rahman, Muhammad Rezamil Aditya; Zulaeha, Mulyani (RIO LAW JURNAL, 2025)
This study discusses the multiple interpretations of public order in the execution of foreign arbitral awards in Indonesia. Article 66(c) of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution does not provide clear explanations and is considered to have overly broad and general interpretations. The lack of a definitive definition allows public order to be exploited as a loophole for grounds to annul the execution of foreign arbitral awards in Indonesia, which in turn creates legal uncertainty in implementing these awards. This research aims to analyze the concept of public order that can serve as a guideline for the execution of foreign arbitral awards in Indonesia. The research method used is normative, addressing the ambiguity of norms regarding public order in Article 66(c) of the Arbitration Law. Based on the analysis using various approaches, the concept of public order is formulated as the fundamental principles and values prevailing in Indonesian society, referring to the values of Pancasila as the ideological and philosophical foundation of the Indonesian nation and the 1945 Constitution as the highest legal basis in the legal system. Furthermore, the multiple interpretations of public order lead to legal uncertainty, causing the international community to view Indonesia as an arbitration-unfriendly state. This study emphasizes the need for revising or enacting new legislation on arbitration to address the ambiguity or legal gaps in the implementation of arbitration and to adapt to contemporary developments. Keywords: Arbitration, Execution of Awards, Legal Certainty, Public Order.